The stress of competition dissociates neural and cortisol homeostasis in elite athletes - Iellamo, F.; Pigozzi, F.; Parisi, A.; Di Salvo, V.; Vago, T.; Norbiato, G.; Lucini, D.; Pagani, M. (The Journal of Sports Medicine and Physical Fitness, 2003)
Aim: Stressful situations affect autonomic nervous system activity and hormonal responses. This study aimed to investigate the effects of the stress of sports competition on both endocrine system functioning and neurovegetative control of heart rate (HR) in elite athletes. Methods: In 7 top-level pentathletes salivary cortisol levels and autoregressive power spectral analysis of HR variability (HRV) were assessed in the morning and in the afternoon on a regular training day (control) and on the day of a competitive selection trial, held 4 weeks apart. Results: HR, as well as low (LF) and high (HF) frequency components of HRV did not differ significantly both between and within the control and the trial days. On the selection day, morning cortisol levels were significant and markedly greater than on the control day and increased further in the afternoon in contrast to the control day, when cortisol levels decreased in the afternoon as expected from the normal diurnal variation. Conclusion: These results would indicate a dissociation of the neural and hypothalamic-pituitary-adrenal axis functioning in response to the stress of competition in elite athletes, and the considerable extent to which competition may alter selectively the physiology of stress-related hormones while sparing autonomic cardiac regulation.